[Leo X. Pont. Max.] - Raffael (1685)
"Triple portrait of Pope Leo X, Giulio de' Medici and Luigi de' Rossi; Leo X sits at centre, wearing the mozzetta, an embroidered robe and the velvet cap (camauro), looking out of the frame, with his hands resting on the table in front of him, near an open book, holding a magnifying glass; he is flanked by Giulio de' Medici and Luigi de' Rossi, who wear their Cardinal robes and stand at right and left, respectively; they occupy an interior space; after Raphael" (BM)